The inflammation-induced down-regulation of plasma Fetuin-A (α2HS-Glycoprotein) in liver results from the loss of interaction between long C/EBP isoforms at two neighbouring binding sites - Gangneux, Christophe (Oxford University Press, 2003)
Fetuin-A is an hepatic protein whose mRNA transiently falls during the inflammatory acute phase via unknown transcriptional mechanisms. Various FETUA promoter/cat constructs transiently transfected in the Hep3B hepatoma cell line allowed us to identify four NF-1 and C/EBP binding sites (N, C) arranged in a 5′-N2-C2-N1-C1-3′ order and required for basal promoter activity. Mutant constructs demonstrated that C1 and C2 but not N1 nor N2 are required for the cytokine-driven down-regulation of the promoter. A variable spacing between C2 and N1 showed that the alignment of the (C1+N1) and (C2+N2) areas is critical for the promoter activity in quiescent but not cytokine-stimulated cells. Co-transfection of a plasmid only producing either a long or short C/EBPβ isoform prevented FETUA regulation by cytokines. Electromobility shift assays with liver nuclear extracts showed that during the acute phase the complexes formed over N1 and N2 are not modified whereas short C/EBPα and -β isoforms replace the long isoforms bound to C1 and C2 in the quiescent liver. Therefore the basal promoter activity requires an interaction between the long C/EBP isoforms bound to C1 and C2 whereas the inflammation-induced down-regulation results from the loss of interaction between the cytokine-induced, short C/EBP isoforms.